The secrets of Mary Bowser - Leveen, Lois, 1968- (New York : William Morrow, 2012)
"Based on the true story of Mary Bowser, a freed slave who returns to Virginia to spy on the Confederates, The secrets of Mary Bowser is the powerful story of a woman who must sacrifice her freedom to truly achieve it"--Provided by publisher.
Includes "P.S. : insights, interviews & more..."
Keywords: Bowser, Mary Elizabeth, -- approximately 1840- -- Fiction; Freedmen -- Fiction; Women spies -- Fiction; United States -- History -- Civil War, 1861-1865 -- Secret service -- Fiction; Biographical fiction